Distribution and abundance of fish and benthic macroinvertebrates in the Poblacion River, Lawaan, Eastern Samar - Roa, Jane Cara Mae N.; dela Cruz, Margarita G. (2017)
High biodiversity has been observed in inland waters such as rivers, lakes, and waterfalls, in the Philippines. This was conducted primarily to determine species composition, richness, and diversity of fishes and benthic macroinvertebrates in Poblacion River, Lawaan, Eastern Samar from the month of January to April 2017. For the ichthyofaunal survey, this study collected 438 individuals comprising 32 species from 24 families. The midstream and downstream parts of the river had the same species richness at N=18. On the other hand, upstream region had 16 species. Gobiidae and Lutjanidae were the most diverse families with 3 different species each. Using Shannon-Weiner's Diversity Index, midstream and downstream regions showed a relatively high index, both at H'-2.89, while upstream biodiversity was at H'=2.77. Sorensen Similarity Index showed that similarity level between regions averaged at 47.93%, which is relatively low. For benthic macroinvertebrates, a total of 238 individuals, 16 species from 13 families were recorded from the different representative sites (upstream, midstream & downstream). Of the 13 families, Neritidae, Pachychilidae, and Portunidae were the most diverse, all with 2 different species each. Diversity indices of the three sites for macroinvertebrate diversity ranged from 0.95-1.72, which are relatively low values. Similarity between sites were low with an average of 17.17%. The baseline data from this study can be used as a basis for future studies on biodiversity in Poblacion River, Lawaan, Eastern Samar.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.